2017
DOI: 10.1007/s10803-017-3172-7
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration of Low-level Information in Autism Spectrum Disorder: Measuring Susceptibility to the Flash-Beep Illusion

Abstract: Previous studies have suggested audiovisual multisensory integration (MSI) may be atypical in Autism Spectrum Disorder (ASD). However, much of the research having found an alteration in MSI in ASD involved sociocommunicative stimuli. The goal of the current study was to investigate MSI abilities in ASD using lowerlevel stimuli that are not socio-communicative in nature by testing susceptibility to auditory-guided visual illusions. Adolescents and adults with ASD and typicallydeveloping (TD)individuals were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…For instance, in some cases individuals with ASD have been found to report fewer McGurk illusions than peers (Bebko et al, 2014; Feldman et al, 2018a; Stevenson et al, 2014c), but in other cases no significant between-group differences are observed (e.g., Keane, Rosenthal, Chun, & Shams, 2010; Saalasti et al, 2012; Saalasti, Tiippana, KĂ€tsyri, & Sams, 2011; Stevenson et al, 2018; Woynaroski et al, 2013a). Similar inconsistencies have been noted using other tasks, such as the flash-beep illusion (e.g., Bao, Doobay, Mottron, Collignon, & Bertone, 2017; Foss-Feig et al, 2010; Keane et al, 2010) and tasks measuring TBWs for audiovisual stimuli (e.g., Foss-Feig et al, 2010; Noel, De Niear, Stevenson, Alais, & Wallace, 2017).…”
Section: Past Findings For Audiovisual Integration In Individuals Witsupporting
confidence: 66%
“…For instance, in some cases individuals with ASD have been found to report fewer McGurk illusions than peers (Bebko et al, 2014; Feldman et al, 2018a; Stevenson et al, 2014c), but in other cases no significant between-group differences are observed (e.g., Keane, Rosenthal, Chun, & Shams, 2010; Saalasti et al, 2012; Saalasti, Tiippana, KĂ€tsyri, & Sams, 2011; Stevenson et al, 2018; Woynaroski et al, 2013a). Similar inconsistencies have been noted using other tasks, such as the flash-beep illusion (e.g., Bao, Doobay, Mottron, Collignon, & Bertone, 2017; Foss-Feig et al, 2010; Keane et al, 2010) and tasks measuring TBWs for audiovisual stimuli (e.g., Foss-Feig et al, 2010; Noel, De Niear, Stevenson, Alais, & Wallace, 2017).…”
Section: Past Findings For Audiovisual Integration In Individuals Witsupporting
confidence: 66%
“…Second, the present study did not include a condition with two flashes and one beep. Bao et al ( 2017 ) employed a SIFI task that included fusion illusion (i.e., two flashes with one beep perceived as one flash) and reported that individuals with ASD experience the fusion illusion more frequently than TD participants, whereas there was no significant group difference for fission illusion (i.e., one flash with two beeps perceived as two flashes). Other studies that reported non-significant differences in fission illusion have included a condition with two flashes and one beep (Foss-Feig et al 2010 ; Stevenson et al 2018b ; van der Smagt et al 2007 ) whereas studies showing lower fission illusion susceptibility in the ASD group did not include a fusion illusion condition (Stevenson et al 2014 ; Kawakami et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed intact low-level MSI-driven RTs facilitation in ASD. Autistic individuals have been found to show MSI effects similar to controls in a pip-and-pop visual search task, as well as in MSI illusion paradigms 31 – 34 . Higher ASD susceptibility to the 2Flashes-1Beep illusion has also been reported (possibly due to an extended temporal binding window) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that attention improves MSI 24 , 25 . The discrepancies in MSI findings in ASD (studies showing intact MSI in ASD 31 – 34 )may suggest that autistic individuals are capable of integrating modalities as long as they actively attend to stimuli, while in controls, MSI facilitation arises spontaneously without the need for strong attentional tone 23 . This finding might bridge the conflicting findings reported previously.…”
Section: Discussionmentioning
confidence: 99%